Novel gadolinium complexes in aqueous solution : characterization, identification and probable structures - Riri, Mohammed; Benjjar, Abdelkhalek; Kamal, Oussama; Hor, Mustapha; Touaj, Khalifa; Hlaibi, Miloudi (International Journal of Advanced Chemistry, 2014)
In this work, we shall present the results of investigations on the interaction of the gadolinium ion (Gd3+) with different chelation sites of mandelic acid and DL-serine (amino acid) formed in dilute solution for pH values between 5.50 and 7.50. The general formula of these new organometallic complexes is and (mandelate ions and: serine ions). These gadolinium complexes detected, are colorless and have no absorption band UV–visible. In this sense, we have used an analytical technique called « Indirect Photometry Detection (IPD) » have identified major di-nucleaire and tri-nuclear complexes of these acids. This technique allowed us to determine the composition and stabilities of complexes predominate in solution, giving for these colorless complexes a molar ration (2:2) and (3:2) for mandilic acid and serine acid respectively, and we have shown that the composition and stability constant depends on the acidity of the medium. To complement previous results and to propose probable structures for these new coloress complexes, IR and Raman spectroscopy have been conducted to identify the different chelation sites for theses ligands. Keywords: Coloress Complexes, DL-Serine, Indirect Photometry Detection, Gadolinium Complexes, Mandelate Ions.